Persepsi Mahasiswa Jurusan Komunikasi Penyiaran Islam Fakultas Dakwah dan Ilmu Komunikasi UIN SU terhadap Partai Politik Islam di Sumatera Utara - Siregar, Syahroni; Paralihan, Hotmatua; Yuzaidi, Yuzaidi (Lembaga Yasin AlSys, 2024)
This research aims to find out that Islamic political parties are organizations that are formed with the aim of winning people's support and controlling government power through competition between groups with different views. Along with the policy of freedom of expression and association through political parties in the reform era. Giving rise to the phenomenon of political parties emerging, including parties with Islamic leanings. The purpose of this research is to determine the perceptions of students majoring in Islamic broadcasting communication, Faculty of Da'wah and Communication Science, UIN SI, towards Islamic political parties in North Sumatra. This research is a qualitative descriptive study with data collection techniques through in-depth semi-structured interviews with 4 informants who are Muslim students majoring in Islamic broadcasting communications at UIN North Sumatra. The results of this research show that based on the perception of students majoring in Islamic broadcasting communication at UIN SU Medan City, there is student participation that students do not just come to the polling station and cast their vote, but also must take part in overseeing the implementation stages. Meanwhile, currently existing parties are considered to no longer represent or contribute to students, but are more likely to contribute to their own parties.